Youth athlete protection in regard to the European sports charter and the code of ethics - von Bothmer, Felix (Department of Commercial Law, 2023)
For many youth athletes sport is an enjoyable activity but not for everyone. Some will have their lives destroyed during those years when they are active in sport. Prevention of the abuse that occurs against children and young people is high on the political agenda in many countries in Europe. Until recently, however, this issue has not received much attention in the sporting arena, probably because sport has been associated by most people with fair play, ethical values and high moral standards. In addition, many sport organisations regarded sport as being on the site of political neutrality. Consequently, they have been slow to embrace the principles of equal rights which are enshrined in other public organisations. In this paper, the various forms of abuse and maltreatment that may occur to youth athletes during their participation in sporting activities are demonstrated while focusing on the one side on sexually and on the other side on commercially motivated abuse of the youth athletes. After pointing out the most prevalent and disturbing consequences of youth athletes abuse in sport, the paper deals with the obligation to protect the young athletes. In this context, the role of the Council of Europe and the responsibility of its member states as well as the parents of the young athletes are analysed. The focus however, will be on the responsibility of the sport organisations, who hold control over the sports movement, to implement policies and procedures. At the end, different measures which may help minimising the abuse of youth athletes are introduced. However, it is clear that not the implementation of a single measure alone may offer an effective protection of the youth athletes but an implementation of a combination of various measures on different levels may enhance the possibility of success in fighting the abuse and harassment of youth athletes in sport.